Nurturing Social Inclusion among Children through Social Media: Exploring Stories of Mothers from Sargodha - Quratulain; Uzair-ul-Hassan, Muhammad; Parveen, Iram (Pakistan Journal of Humanities and Social Sciences, 2023)
Early childhood connections of children have a big impact on their grownup lives. Social media and peer relationships are two aspects of early life that have rapidly grown in recent years. Social media have been significantly impacting young learners over the past few years. In order to better understand how social media can foster social inclusion in early childhood and connect with peers, our study examined the experiences of twenty mothers. Stories of social connections at home and at school emerged from interviews with mothers whose children attended private schools in Sargodha city. Working within the qualitative paradigm, the data received from mothers was analyzed. Initial coding derived us to surface categories and themes. Based on the study's findings, it was revealed that using social media responsibly and positively can foster social inclusion for establishing peer connections in the early years of childhood. Social media promote social interaction, social involvement and collaboration among children. The study further revealed the influential effects of social media on children's social inclusion with respect to communication, self-confidence, and feelings of togetherness in distanced spaces to overcome social isolation.